Multidimensional model of assessment of economic thinking in college students (2014)
The Economic Thinking in undergraduates is a strategic aspect of research in the framework of higher education, given its critical impact on the development of skills and professional standards expected in front of the Scientific and Technological Innovation. The main contribution of this study focuses on the development of a Multidimensional Model of Assessment of Economic Thinking, from the perspective of Self-Organizing Systems. The methodology has an approach empirical-analytic. In relation to the instruments and results correspond to a perspective of Adaptative System based in Item Response Theory (IRT), Complexity Theory and Fractal Models (L-system) about the competence in solving economic problems, knowledge of financial aspects, responsible consumption, sustainable development, and the attitudes to understanding the economic world.